Heat and Mass Transfer Effect on MHD Flow of a Viscoelastic Fluid through a Porous Medium Bounded by an Oscillating Porous Plate in Slip Flow Regime - S. N. Sahoo (International Journal of Chemical Engineering)
Unsteady flow of an eclectically conducting and incompressible viscoelastic liquid of the Walter model with simultaneous heat and mass transfer near an oscillating porous plate in slip flow regime under the influence of a transverse magnetic field of uniform strength is presented. The governing equations of the flow field are solved by a regular perturbation method for small elastic parameter, and the expressions for the velocity, temperature, concentration, skin friction , the heat flux in terms of the Nusselt number , and the rate of mass transfer in terms of the Sherwood number are obtained. The effects of the important flow parameters on the dynamics are discussed. Findings of the study reveal that the rarefaction parameter accelerates the fluid particles in the flow domain. Elastic parameter contributes to sudden fall of the velocity near the plate. Magnetic force contributes to greater skin friction as the time elapses. Destructive reaction reduces, whereas generative reaction enhances the concentration distribution.